Information System for Financial Management and Human Resource Proficiency and Accountability for Financial Statements: An Indonesian Case Study - Soesiawan, Tri Pangkat; Lestari, Laraswati Puji; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
The purpose of this study is to investigate how organizational culture, human resource competency, and financial management information system variables affect the financial reporting responsibility of village governments. Using a straightforward random sample method, 65 villages from the two districts made up the sample. The data from this study were analyzed using multiple regression analysis. The outcomes demonstrated that Human resource competency, organizational culture, and financial management information systems—the three differentiators in the two districts—have a major positive impact on accountability when it comes to creating village government financial reports in Tabanan Regency. In Badung Regency, on the other hand, organizational culture has little bearing because work cultures vary throughout village governments. Local culture serves as the foundation for organizational culture in the Tabanan regency, whereas organizational culture in the Badung regency is examined and implemented differently, suggesting that no organizational culture type is better than any other. This implies that depending on how and when organizational goals are to be achieved, all types can work together and in tandem with one another.